Obesity and inflammatory arthritis: impact on occurrence, disease characteristics and therapeutic response. Issue 1 (29th June 2015) - Daïen, Claire I; Sellam, Jérémie
Abstract : Overweight and obesity are increasing worldwide and now reach about one-third of the world's population. Obesity also involves patients with inflammatory arthritis. Knowing the impact of obesity on rheumatic diseases (rheumatoid arthritis, ankylosing spondylitis and psoriatic arthritis) is thus an important issue. This article first reviews the epidemiological and clinical data available on obesity in inflammatory rheumatic diseases, that is, its impact on incident disease, disease characteristics and the therapeutic response. The second part of this review gives an overview of the factors potentially involved in the specifics of inflammatory arthritis in patients with obesity, such as limitations in the clinical assessment, diet, microbiota and adipokines.